MENATA PENDIDIKAN ISLAM DI INDONESIA (Sebuah Upaya Menuju Pendidikan yang Memberdayakan) - Ibrahim, Sulaiman (State Institute of Islamic Studies (IAIN) Palu, 2011)
Abstract: In the era of reformation, the Islamic education faces two problems: the demand of Indonesian community on the quality of Islamic education and the education irrelevance to community development. In addition, the ability of Indonesian nation in managing Islamic education is still not adequate so that Islamic educaion has no clear vision and missions. In line with the national education problems facing the globalization era, the very open world era. In this regard, the Indonesia nation must establish an adequate ability in the framework of cooperation and competition with other nations. Through cooperation and competition, the Indoesnia nastion will be able to enhance the quality of Indonesia people.Kata Kunci: pendidikan Islam, pendidikan yang memberdayakan, Total Quality Management (TQM)